2005
DOI: 10.2224/sbp.2005.33.1.19
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Social Skills and Loneliness Levels of University Students With Respect to Their Attachment Styles in a Sample of Turkish Students

Abstract: This study investigated the effects of attachment styles of university students on their social skills and loneliness levels. Their social skill levels, loneliness levels and attachment styles were measured by the Social Skills Inventory, UCLA Loneliness Scale, and Relationships Scale Questionnaire respectively. To analyze data. Mest. correlation analysis, and regression analysis were employed. Emotional expressivity levels, emotional sensitivity levels, social control levels, and total social skill levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
51
1
15

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 17 publications
14
51
1
15
Order By: Relevance
“…Deniz et al in a study showed that there was a significant relationship between loneliness and marital status (23). However, our study did not indicate a significant relationship between loneliness and marital status.…”
Section: Discussioncontrasting
confidence: 88%
“…Deniz et al in a study showed that there was a significant relationship between loneliness and marital status (23). However, our study did not indicate a significant relationship between loneliness and marital status.…”
Section: Discussioncontrasting
confidence: 88%
“…Considering that people with fearful attachment style do not trust themselves but others (Bartholomew & Horowitz, 1991), it is not surprising that they are open to social sensitivity. The study by Deniz, Hamarta and Ari (2005) supports this finding.…”
Section: Discussionsupporting
confidence: 67%
“…It was also found that fearful and dismissing attachment style predicted emotional sensitivity skill, and preoccupied attachment style predicted social control. Deniz, Hamarta and Ari (2005) found that secure attachment affected emotional expressivity and social expressivity, but it did not affect other sub-dimensions of social skills. Besides, they found that other attachment styles did not affect social skills.…”
Section: Discussionmentioning
confidence: 84%
“…Allen ve arkadaşları (2002) tarafından yapılan ve 2 yıl boyunca devam eden başka bir çalışmada ise 16-18 yaş arasındaki ergenlerin bağlanma güvenliğinin sosyal becerileri arttırdığı, kaygılı-kararsız bağlanma türünün ise bu dönemde suça yönelik davranışları arttırdığı; kaygılı bağlanmış olan ergenlerin sosyal beceri düzeylerinin önemli ölçüde azaldığı ve suça yönelik davranışlarının arttığı bulunmuştur. Alanyazında yer alan pek çok araştırmada sosyal becerilerle bağlanma arasında anlamlı ilişkiler bulunmuştur (DiTommaso ve ark., 2003;Kumru, Carlo ve Edwards, 2004;Deniz, Hamarta ve Ari, 2005). Araştırmannın bulgusuyla paralel olan bu çalışmalardan da yola çıkı-larak bağlanma güvenliğinin sosyal beceri düzeyini etkilediği söylenebilir.…”
Section: Discussionunclassified